The Level of Anxiety of Hypertension Patients Against Covid-19 Disease with Repeat Visits of Hypertensive Patients During the Covid-19 Pandemic - Indarwati Indarwati; Ahmad Asyrofi; Triana Arisdiani (Global Health Science Group, 2022)
Hypertension is the comorbidity that causes the most deaths due to positive cases of Covid-19, with a reality like this, residents who suffer from hypertension to take control every month of course feel anxiety during a pandemic like now, even though hypertension sufferers have to take medicine every day and control it. routinely. The purpose of this study was to determine the relationship between the anxiety level of Hypertension patients against Covid-19 disease with repeat visits of Hypertensive patients during the Covid-19 pandemic at the Brangsong II Health Center. This study uses a descriptive correlation study design, a sample of 85, the sampling technique using Consecutive sampling. Statistical analysis using chi-square. The results showed that the majority of respondents aged 51-60 years were 68.2%, 45.9% had elementary school education, 65.9% were female, and 25.9% worked as farmers. The average length of time patients suffer from hypertension is 5 years, a minimum of 2 years and a maximum of 20 years, patients experiencing severe anxiety as much as 47.1%, non-routine repeat visits as much as 63.5% and there is a relationship between the level of anxiety of hypertensive patients with Covid-19 disease. 19 with repeat visits of Hypertensive patients during the pandemic with p value = 0.003 (P < 0.05). It is hoped that it can provide information as a basis for managing anxiety and the psychological impact of Covid-19 on hypertensive patients